Reply to a comment by Watras et al. (2014) on temperature compensation method for field measurements of CDOM fluorescence. (30th July 2015) - Ryder, Elizabeth; Jennings, Eleanor; de Eyto, Elvira; Dillane, Mary; Nic Aonghusa, Caitriona; Pierson, Donald C.; Moore, Karen; Rouen, Martin; Poole, Russell
Abstract The recent comment by Watras et al. (2014) clarifies the calculation of the temperature correction coefficient (ρ) in Watras et al. (2011). Based on this clarification, we accept that the equation to compensate for temperature quenching of chromophoric dissolved organic matter (CDOM) fluorescence presented in Ryder et al. (2012) and the equation proposed in Watras et al. (2011) are mathematically equivalent.